(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Respiratory diseases pose a significant challenge to global health, with smoking being a key risk factor. Chronic respiratory conditions like chronic obstructive pulmonary disease (COPD) and asthma are particularly affected by smoking, which accelerates the decline in lung function. Objectives The study aims to compare the respiratory function outcomes between smokers and non-smokers with respiratory disorders and to determine the impact of age, gender and BMI on the lung function. Methods Pulmonary function test (PFT) data of 438 patients from King Abdulaziz University Hospital (KAUH) was retrospectively studied. Spirometry measurements were FVC Actual, FEV1 Actual, and FEV1/FVC ratio. The descriptive statistics and multivariate analysis (MANOVA) were applied to analyse data using SPSS version 27. Results Of all the participants, only 7.3% were smokers, while remaining 92.7% were non-smokers. Although, the FEV1/FVC ratio was slightly lower in non-smokers (p=0.021) as compared to smokers in diseased participants, but most spirometry measures showed non-significant statistical difference (p>0.05) between the groups. Whereas, there was a significant statistical difference (p<0.05) for FEV1 and FEV1/FVC when genderbased comparison was observed. Conclusion Significant effect of smoking was seen in some lung function effects when analyzed by gender and BMI. Differences between smokers and non-smokers were not significant throughout normal and diseased groups except FEV1/FVC. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S345-S350